Fiscal Consolidation and Australia's Public Debt. Issue 4 (23rd September 2016) - Makin, Anthony J.; Pearce, Julian
Abstract : Australia has experienced one of the fastest growing public debt levels in the world post‐Global Financial Crisis due to a series of large federal budget deficits driven by high government spending. In this paper we examine the balance sheet implications of this escalating public debt, before proposing some macro‐fiscal objectives for determining its sustainable level. These objectives are to (i) restore the federal government's solvency; (ii) eliminate foreign public debt; and (iii) achieve budgetary balance over the business cycle. Empirically, we first examine how much fiscal consolidation is required for debt stabilisation at current levels, before considering what sized budget balances are needed to achieve the target debt to GDP ratios consistent with the proposed objectives. The results show that no target debt to GDP level consistent with the optimal levels will be met on current fiscal settings in the medium term. This implies significantly greater fiscal consolidation is required to minimise future fiscal risk. Abstract : This paper examines Australia's public debt with reference to the federal government's balance sheet, foreign borrowing and cyclical balance. It provides evidence that greater fiscal consolidation is required to achieve debt to GDP levels consistent with sustainable target levels over the medium term.